Analysis of Copper (Cu) Heavy Metal in Aquatic Plants as an Indicator of Pollution in Brantas Mojokerto River - Masruroh, Siti; Purnomo, Tarzan (LenteraBio : Berkala Ilmiah Biologi, 2023)
The Brantas river is one of the rivers that play a significant role in various sectors of East Java. The Brantas river in Mojokerto region is potentially contaminated because it receives waste disposal from drainage basin (DAS) of Brantas River, which contains various substances and materials that can pollute the river, including heavy metal copper (Cu). This study aimed to determine Cu levels in water and aquatic plants, analyze the relationship between Cu levels in water and aquatic plants, and determine the quality of river water in terms of physical and chemical parameters. Sampling was carried out at three stations on Jalan Hayam Wuruk and Jalan Mayjend Sungkono Mojokerto. Testing for Cu heavy metal content was performed using Atomis Absorption Spectrophotometry (AAS) method. Data were analyzed descriptively quantitatively, water Cu content and physical-chemical parameters were compared with PP RI No. 22 of 2021, the Cu levels of aquatic plants were compared with the Decree of the Directorate General of Drug and Food Control No: 03725/BSK/VII/89, and statistical correlation test to determine the relationship between Cu levels in water and aquatic plants. The results showed that Cu levels in water was 0,272±0,023 ppm – 0,311±0,019 ppm, water spinach (Ipomoea aquatica) 0,315±0,020 ppm – 0,333±0,030 ppm, water hyacinth (Eichhornia crassipes) 0,229±0,015 ppm – 0,258±0,013 ppm, and genjer (Limnocharis flava) 0,232±0,023ppm – 0,253±0,008 ppm. No correlation was found between Cu levels of water and aquatic plants. Water quality based on physical and chemical parameters was classified as good.